Legal Consequences on Sirri Marriage Performers Without the Permission of the First Wife: Perspective of Islamic Law and Positive Law - Dodoteng, Harisman; Abidin, Abidin; Musyahidah, Sitti (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC LAW AND SOCIETY, 2023)
The aim of this study is to examine the existence of sirri marriages occasionally. Some people even do it without the first wife's permission, resulting in losses for the perpetrators even though the law has determined that marriage must be brought before the official marriage registrar to be registered. On this issue, the researchers focused on investigating the legal consequences for sirri marriage perpetrators without the first wife's permission and the perspective of Islamic law and positive law for sirri marriage perpetrators without the first wife's consent. The provisions for sirri marriage in Islamic law are not found in the Al-Quran and Hadith. Sirri marriage can be made a criminal act in Islamic law, but the provisions fall into jarimah ta'zir. The ta'zir punishment is not directly found in the Al-Quran and Hadith, this type of punishment becomes the judge's or local government's competence. Meanwhile, according to the positive law of sirri marriages that do not comply with or follow the legal procedures for marriage or without asking for the first wife's permission, the marriage can be punished under Article 279. This type of research used a literature review. The researchers suggest that this university should socialize regarding this matter, and registration of marriages must continue to be carried out by the government and the community, in this case, religious leaders.